The Environmental, Public Health, and Human Rights Impacts on Enhancing the Quality of Life of People with Intellectual Disability - Sanchez, Laura Elisabet Gomez (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Societal views on the human rights of persons with disabilities have significantly changed over the last four decades. However, while achieving equality, autonomy, nondiscrimination, participation, and inclusion should be a priority, abuses and violations of rights often occur in the most immediate environments of people with intellectual disability. This book is intended to provide greater visibility to people with intellectual disability, as full subjects of rights and improve their quality of life from a perspective of human rights, citizenship, and contextual analysis. We discuss the role of context, the provision of inclusive environments, and the improved health status at promoting quality of life-related personal outcomes and enhancing quality of life and equality for people with intellectual disability.